Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Detection and Control of Spin-Orbit Interactions in a GaAs Hole Quantum Point Contact - Srinivasan, A.; Miserev, D. S.; Hudson, K. L.; Klochan, O.; Muraki, K.; Hirayama, Y.; Reuter, Dirk; Wieck, A. D.; Sushkov, O. P.; Hamilton, A. R. (Physical Review Letters)

Local Algorithms for the Continuous Gathering Problem - Podlipyan, Pavel

Scheduling with Scarce Resources - Riechers, Sören

Cost-efficient Scheduling on Machines from the Cloud - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören (Journal of Combinatorial Optimization)

Knowledge-based Verification of Service Compositions - Walther, Sven

Minimizing downtimes: Using dynamic reconfiguration and state management in SDN - Schwabe, Arne; Rojas, Elisa; Karl, Holger (2017 IEEE Conference on Network Softwarization, NetSoft 2017, Bologna, Italy, July 3-7, 2017)

Demo: OpenC2X — An open source experimental and prototyping platform supporting ETSI ITS-G5 - Laux, Sven; Pannu, Gurjashan Singh; Schneider, Stefan Balthasar; Tiemann, Jan; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2016 IEEE Vehicular Networking Conference (VNC))

Predicting Rankings of Software Verification Tools - Czech, Mike; Hüllermeier, Eyke; Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 3rd International Workshop on Software Analytics)
Today, software verification tools have reached the maturity to be used for large scale programs. Different tools perform differently well on varying code. A software developer is hence faced with the problem of choosing a tool appropriate for her program at hand. A ranking of tools on programs could facilitate the choice. Such rankings can, however, so far only be obtained by running all considered tools on the program.In this paper, we present a machine learning approach to predicting rankings of tools on programs. The method builds upon so-called label ranking algorithms, which we complement with appropriate kernels providing a similarity measure for programs. Our kernels employ a graph representation for software source code that mixes elements of control flow and program dependence graphs with abstract syntax trees. Using data sets from the software verification competition SV-COMP, we demonstrate our rank prediction technique to generalize well and achieve a rather high predictive accuracy (rank correlation > 0.6).

SONATA: Service programming and orchestration for virtualized software networks - Dräxler, Sevil; Karl, Holger; Peuster, Manuel; Razzaghi Kouchaksaraei, Hadi; Bredel, Michael; Lessmann, Johannes; Soenen, Thomas; Tavernier, Wouter; Mendel-Brin, Sharon; Xilouris, George (2017 IEEE International Conference on Communications Workshops (ICC Workshops))
In conventional large-scale networks, creation and management of network services are costly and complex tasks that often consume a lot of resources, including time and manpower. Network softwarization and network function virtualization have been introduced to tackle these problems, aiming at decreasing costs and complexity of implementing new services, maintaining the implemented services, and managing available resources in service provisioning platforms and underlying infrastructures. To experience the full potential of these approaches, innovative development support tools and service provisioning environments are needed. To answer these needs, we introduce the architecture of the open-source SONATA system, a service programming, orchestration, and management framework. We present a development toolchain for virtualized network services, fully integrated with a service platform and orchestration system. We introduce the modular and flexible architecture of our system and discuss its main components and features, such as function- and service-specific managers that allow fine-grained service management, slicing support to facilitate multi-tenancy, recursiveness for improved scalability, and full-featured DevOps support.

Predicting Rankings of Software Verification Competitions - Czech, Mike; Hüllermeier, Eyke; Jakobs, Marie-Christine; Wehrheim, Heike
Software verification competitions, such as the annual SV-COMP, evaluate software verification tools with respect to their effectivity and efficiency. Typically, the outcome of a competition is a (possibly category-specific) ranking of the tools. For many applications, such as building portfolio solvers, it would be desirable to have an idea of the (relative) performance of verification tools on a given verification task beforehand, i.e., prior to actually running all tools on the task.In this paper, we present a machine learning approach to predicting rankings of tools on verification tasks. The method builds upon so-called label ranking algorithms, which we complement with appropriate kernels providing a similarity measure for verification tasks. Our kernels employ a graph representation for software source code that mixes elements of control flow and program dependence graphs with abstract syntax trees. Using data sets from SV-COMP, we demonstrate our rank prediction technique to generalize well and achieve a rather high predictive accuracy. In particular, our method outperforms a recently proposed feature-based approach of Demyanova et al. (when applied to rank predictions).

A flexible multi-pop infrastructure emulator for carrier-grade MANO systems - Peuster, Manuel; Dräxler, Sevil; Razzaghi Kouchaksaraei, Hadi; van Rossem, Steven; Tavernier, Wouter; Karl, Holger (IEEE Conference on Network Softwarization, NetSoft 2017, Bologna, Italy, July 3-7, 2017)
Developing a virtualized network service does not only involve the implementation and configuration of the network functions it is composed of but also its integration and test with management solutions that will control the service in its production environment. These integration tasks require testbeds that offer the needed network function virtualization infrastructure~(NFVI), like OpenStack, introducing a lot of management and maintenance overheads. Such testbed setups become even more complicated when the multi point-of-presence~(PoP) case, with multiple infrastructure installations, is considered. In this demo, we showcase an emulation platform that executes containerized network services in user-defined multi-PoP topologies. The platform does not only allow network service developers to locally test their services but also to connect real-world management and orchestration solutions to the emulated PoPs. During our interactive demonstration we focus on the integration between the emulated infrastructure and state-of-the-art orchestration solutions like SONATA or OSM.

PART_PW: From Partial Analysis Results to a Proof Witness - Jakobs, Marie-Christine (Software Engineering and Formal Methods)
Today, verification tools do not only output yes or no, but also provide correctness arguments or counterexamples. While counterexamples help to fix bugs, correctness arguments are used to increase the trust in program correctness, e.g., in Proof-Carrying Code (PCC). Correctness arguments are well-studied for single analyses, but not when a set of analyses together verifies a program, each of the analyses checking only a particular part. Such a set of partial, complementary analyses is often used when a single analysis would fail or is inefficient on some program parts.We propose PART_PW, a technique which allows us to automatically construct a proof witness (correctness argument) from the analysis results obtained by a set of partial, complementary analyses. The constructed proof witnesses are proven to be valid correctness arguments and in our experiments we use them seamlessly and efficiently in existing PCC approaches.

OpenCL-basierte Videoverarbeitung auf heterogenen Rechenknoten - Knorr, Christoph

Inklusive Bildung zwischen Beruflichkeit und Subjektorientierung - Eine Analyse ausbildungsvorbereitender Bildungsgänge - Frehe, Petra; Kremer, H.-Hugo (Potenzialorientierte Förderung in den Fachdidakten)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

MatchBox: A Framework for Dynamic Configuration of Service Matching Processes (Extended Abstract) - Platenius, Marie Christin; Arifulina, Svetlana; Schäfer, Wilhelm (Tagungsband Software Engineering)
The increasing popularity of paradigms like service-oriented computing and cloud com-puting is leading to a growing amount of service providers offering software componentsin the form of deployed, ready-to-use services (Software as a Service, SaaS) [14, 20].In order to discover and select software services, intermediaries apply service matchingapproaches for determining whether the specification of a provided service satisfies therequester’s requirements. There are already lots of different service matching approachesconsidering different service properties (structural, behavioral, and non-functional proper-ties). However, each of these approaches alone is not enough to provide a high matchingresult quality (e.g., accurate matching results) [BOR04].Thus, such approaches should be combined into a more holistic approach leading to moreaccurate matching results. However, this combination is a manual, error-prone procedurewhere many design decisions are made. Furthermore, this procedure has to be repeatedfrequently depending on the context, e.g., to consider different requesters or markets.

Literaturüberblick über die Rolle von Business Architecture in Enterprise Architecture - Lohrsträter, Lukas

Perceived Competence and Incompetence in the First Year of Mathematics Studies: Forms and Situations - Liebendörfer, Michael; Hochmuth, Reinhard (Didactics of Mathematics in Higher Education as a Scientific Discipline - Conference Proceedings)

Interest development during the first year at university: do mathematical beliefs predict interest in mathematics? - Liebendörfer, Michael; Schukajlow, Stanislaw (ZDM)

Kartellabsprachen und vertikale Preisbindungen - Eine wettbewerbspolitische Analyse am Bespiel der Lebensmittelindustrie in Deutschland - Niggemeyer, Laura

Joint Optimization of Scaling and Placement of Virtual Network Services - Dräxler, Sevil; Karl, Holger; Mann, Zoltan Adam (Proceedings of the 17th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing (CCGrid 2017))
Management of complex network services requires flexible and efficient service provisioning as well as optimized handling of continuous changes in the workload of the service.To adapt to changes in the demand, service components need to be replicated (scaling) and allocated to physical resources (placement) dynamically. In this paper, we propose a fullyautomated approach to the joint optimization problem of scaling and placement, enabling quick reaction to changes. We formalize the problem, analyze its complexity, and develop two algorithms to solve it. Extensive empirical results show the applicability andeffectiveness of the proposed approach.

Gradient-Based Multiobjective Optimization with Uncertainties - Peitz, Sebastian; Dellnitz, Michael (NEO 2016)
In this article we develop a gradient-based algorithm for the solution of multiobjective optimization problems with uncertainties. To this end, an additional condition is derived for the descent direction in order to account for inaccuracies in the gradients and then incorporated into a subdivision algorithm for the computation of global solutions to multiobjective optimization problems. Convergence to a superset of the Pareto set is proved and an upper bound for the maximal distance to the set of substationary points is given. Besides the applicability to problems with uncertainties, the algorithm is developed with the intention to use it in combination with model order reduction techniques in order to efficiently solve PDE-constrained multiobjective optimization problems.

Instantiating a Predicate Encryption Scheme via Pair Encodings - Ganesh Athreya, Advait

Towards Encrypted MPC for Linear Constrained Systems - Schulze Darup, Moritz; Redder, Adrian; Shames, Iman; Farokhi, Farhad; Quevedo, Daniel (IEEE Control Systems Letters)

Presentation: Framework for Constructing Context-Specific Migration Methods for Test Cases - Jovanovikj, Ivan

Acceptance of Mobile Learning at SMEs of the Service Sector - Beutner, Marc; Rüscher, Frederike Anna (Proceedings of the 13th International Conference Mobile Learning 2017)

Die Unterstützung von Entrepreneurship im Kultur- und Kreativsektor durch Berufsbildung - Beutner, Marc; Rüscher, Frederike Anna (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Green Economy und Green Entrepreneurship fördern – GET-UP Ergebnisse - Beutner, Marc; Rüscher, Frederike Anna (Kölner Zeitschrift für Wirtschaft und Pädagogik)

YES – Ein Online Gruppen-Deck-Card-Game zu European Citizenship - Beutner, Marc; Eggert, Denise; Rüscher, Frederike Anna (Hochschultage 2017)

Aktive Feedbacklösungen im Unterricht: Das Class-Room-Response-System PINGO - Beutner, Marc (Hochschultage 2017)

Webbasierte Classroom Response Systeme in der Hochschullehre – Eine designbasierte Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Beutner, Marc; Zoyke, A; Herrmann, P; Kundisch, Dennis; Magenheim, J; Neugebauer, J (Das Hochschulwesen)

Indikatorbasierte Erkennung und Kompensation von ungenauen und unvollständig beschriebenen Softwareanforderungen - Bäumer, Frederik Simon
The vision of OTF Computing is to have the software needs of end users in the future covered by an automatic composition of existing software services. Here we focus on natural language software requirements that end users formulate and submit to OTF providers as requirement specifications. These requirements serve as the sole foundation for the composition of software; but they can be inaccurate and incomplete. Up to now, software developers have identified and corrected these deficits by using a bidirectional consolidation process. However, this type of quality assurance is no longer included in OTF Computing - the classic consolidation process is dropped. This is where this work picks up, dealing with the inaccuracies of freely formulated software design requirements. To do this, we developed the CORDULA (Compensation of Requirements Descriptions Using Linguistic Analysis) system that recognizes and compensates for language deficiencies (e.g., ambiguity, vagueness and incompleteness) in requirements written by inexperienced end users. CORDULA supports the search for suitable software services that can be combined in a composition by transferring requirement specifications into canonical core functionalities. This dissertation provides the first-ever method for holistically recording and improving language deficiencies in user-generated requirement specifications by dealing with ambiguity, incompleteness and vagueness in parallel and in sequence.

Geschäftsmodell-Frameworks zur Analyse und Klassifikation bestehender Geschäftsmodelle - Warkentin, Markus

Optimal Security Proofs for Full Domain Hash, Revisited - Kakvi, Saqib; Kiltz, Eike (Journal of Cryptology)

Highly efficient frequency conversion with bandwidth compression of quantum light - Allgaier, Markus; Ansari, Vahid; Sansoni, Linda; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Harder, Georg; Brecht, Benjamin; Silberhorn, Christine (Nature Communications)

Waveguide Cavity Resonator as a Source of Optical Squeezing - Stefszky, Michael; Ricken, R.; Eigner, Christof; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)

Narrative Ethics and Dementia in Alice LaPlante’s Turn of Mind - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Introduction - Strauß, Sara (Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives)

Neuroethical Reflections on Body and Awareness in Kazuo Ishiguro’s Never Let Me Go and Ian McEwan’s Saturday - Strauß, Sara (Presence of the Body: Awareness In and Beyond Experience)

Fabrication of low-loss Rb-exchanged ridge waveguides in z-cut KTiOPO_4 - Volk, Martin F.; Rüter, Christian E.; Santandrea, Matteo; Eigner, Christof; Padberg, Laura; Herrmann, Harald; Silberhorn, Christine; Kip, Detlef (Optical Materials Express)

A monolithic, doubly-resonant parametric down-conversion source for Caesium Raman memories - Brecht, Benjamin; Lazo-Arjona, O.; Kaczmarek, K. T.; Parker, T.; Ricken, R.; Quiring, V.; Eigner, Christof; Luo, K. H.; Herrmann, Harald; Silberhorn, Christine; Walmsley, I. A. (Frontiers in Optics 2017)

Waveguide Cavity Resonator as a Source of Optical Squeezing - Stefszky, M.; Ricken, R.; Eigner, Christof; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)

A two-channel, spectrally degenerate polarization entangled source on chip - Sansoni, Linda; Luo, Kai Hong; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (npj Quantum Information)

The Immobility of Power in British Political Theatre after 2000: Absurdist Dystopias - Tönnies, Merle (Journal of Contemporary Drama in English)

Still/Again 'Political'? New Approaches to Questioning Power in Mike Bartlett's 13 (2011) - Tönnies, Merle (Finance, Terror, and Science on Stage. Current Public Concerns in 21st-Century British Drama)

Pope, G.: Reading London's Suburbs - Tönnies, Merle (Anglistik. International Journal of English Studies)

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Bäumer, Frederik Simon; Platenius, Marie Christin; Geierhos, Michaela; Hamann, Heiko; Engels, Gregor (2017 IEEE 25th International Requirements Engineering Conference Workshops (REW))
Bridging the gap between informal, imprecise, and vague user requirements descriptions and precise formalized specifications is the main task of requirements engineering. Techniques such as interviews or story telling are used when requirements engineers try to identify a user's needs. The requirements specification process is typically done in a dialogue between users, domain experts, and requirements engineers. In our research, we aim at automating the specification of requirements. The idea is to distinguish between untrained users and trained users, and to exploit domain knowledge learned from previous runs of our system. We let untrained users provide unstructured natural language descriptions, while we allow trained users to provide examples of behavioral descriptions. In both cases, our goal is to synthesize formal requirements models similar to statecharts. From requirements specification processes with trained users, behavioral ontologies are learned which are later used to support the requirements specification process for untrained users. Our research method is original in combining natural language processing and search-based techniques for the synthesis of requirements specifications. Our work is embedded in a larger project that aims at automating the whole software development and deployment process in envisioned future software service markets.
Keywords: Software; Unified modeling language; Requirements engineering; Ontologies; Search problems; Natural languages

Dementia and Subjectivity. Aesthetic, Literary and Philosophical Perspectives

Fragments of a Life Remembered: Fragmentation and Silences in Dementia Narratives - Strauß, Sara (Narrative and Mental Health)

From Open API to Semantic Specifications and Code Adapters - Schwichtenberg, Simon; Gerth, Christian; Engels, Gregor (Proceedings of the 24th IEEE International Conference on Web Services (ICWS))
Today, modern IT-systems are often an interplay of third-party web services. Developers in their role as requesters integrate existing services of different providers into new IT-systems. Providers use frameworks like Open API to create syntactic service specifications from which requesters generate code to integrate services. Proper service discovery is crucial to identify usable services in the growing plethora of third-party services. Most advanced service discovery approaches rely on semantic specifications, e.g., OWL-S. While semantic specification is crucial for a precise discovery, syntactical specification is needed for service invocation. To close the gap between semantic and syntactic specifications, service grounding establishes links between the semantic and syntactic specifications. However, for a large number of web services still no semantic specification or grounding exists. In this paper, we present an approach that semi-automates the semantic specification of web services for service providers and additionally helps service requesters to leverage semantic web services. Our approach enables a higher degree of automation than other approaches. This includes the creation of semantic specifications and service groundings for service providers as well as the integration of services for requesters by using our code generator. As proof-of-concept, we provide a case study, where we derive a sophisticated semantic OWL-S specification from a syntactic Open API specification.

Profile Your Chains, Not Functions. Automated Network Service Profiling in DevOps Environments - Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualisation and Software Defined Networks (NFV-SDN))
Benchmarking and profiling virtual network functions (VNFs) generates input knowledge for resource management decisions taken by management and orchestration systems. Such VNFs are usually not executed in isolation but are often deployed as part of a service function chain (SFC) that connects single functions into complex structures. To manage such chains, isolated performance profiles of single functions have to be combined to get insights into the overall behavior of an SFC. This becomes particularly challenging in highly agile DevOps environments in which profiling processes need to be fully automated and detailed insights about a chain's internal structures are not always available. In this paper, we introduce a fully automatable, flexible, and platform-agnostic profiling system that allows to profile entire SFCs at once. This obviates manual modeling procedures to combine profiling results from single VNFs to reflect SFC performance. We use a case study with different SFC configurations to show that it is hard to model the resulting SFC performance based on single-VNF measurements and that performance interactions between real, non-trivial functions that are deployed in a chain exist.

Assessing Genetic Algorithms for Placing Flow Processing-aware Control Applications - Auroux, Sébastien; Scholz, S.; Karl, Holger (Proc. European Wireless)

Full statistical mode reconstruction of a light field via a photon-number-resolved measurement - Burenkov, I. A.; Sharma, A. K.; Gerrits, T.; Harder, G.; Bartley, Tim; Silberhorn, Christine; Goldschmidt, E. A.; Polyakov, S. V. (Physical Review A)

Limits on the heralding efficiencies and spectral purities of spectrally filtered single photons from photon-pair sources - Meyer-Scott, Evan; Montaut, Nicola; Tiedau, Johannes; Sansoni, Linda; Herrmann, Harald; Bartley, Tim; Silberhorn, Christine (Physical Review A)

"A variational formulation for fuzzy analysis in continuum mechanics" - Mahnken, Rolf (Mathematics and Mechanics of complex systems)
In order to improve the credibility of modern simulation tools, uncertainties of different kinds have to be considered. This work is focused on epistemic uncertainties in the framework of continuum mechanics, which are taken into account by fuzzy analysis. The underlying min-max optimization problem of the extension principle is approximated by α-discretization, resulting in a separation of minimum and maximum problems. To become more universal, so-called quantities of interest are employed, which allow a general formulation for the target problem of interest. In this way, the relation to parameter identification problems based on least-squares functions is highlighted. The solutions of the related optimization problems with simple constraints are obtained with a gradient-based scheme, which is derived from a sensitvity analysis for the target problem by means of a variational formulation. Two numerical examples for the fuzzy analysis of material parameters are concerned with a necking problem at large strain elastoplasticity and a perforated strip at large strain hyperelasticity to demonstrate the versatility of the proposed variational formulation.
Keywords: fuzzy analysis; α-level optimization; quantities of interest; optimization with simple constraints; large strain elasticity; large strain elastoplasticity

,,Identification of Material Parameters for Constitutive Equations “ - Mahnken, Rolf (Encyclopedia of Computational Mechanics)

Fault localization in service compositions - Wehrheim, Heike (Proceedings of the 14th International Conference on Formal Aspects of Component Software (FACS))

Three-Stage Power System Restoration Methodology Considering Renewable Energies - Shen, Cong; Kaufmann, Paul; Braun, Martin (Elsevier International Journal of Electrical Power and Energy Systems (IJEPES))
This is a study of a combined load restoration and generator start-up procedure. The procedure is structured into three stages according to the power system status and the goal of load restoration. Moreover, for each load restoration stage, the proposed algorithm determines a load restoration sequence by considering renewable energy such as solar and wind park to achieve objective functions. The validity and performance of the proposed algorithm is demonstrated through simulations using IEEE-39 network.
Keywords: Load restorationRestoration stageRenewable energyVoltage/frequency fluctuations

"A POSSIBILISTIC APPROACH FOR LINEAR ISOTROPIC ELASTICITY USING THE FUZZY FINITE ELEMENT METHOD" - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (Proceedings of the 2nd International Conference on Uncertainty Quantification in Computational Sciences and Engineering (UNCECOMP 2017))

Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente - Bender, Amelie; Kaul, Thorben; Sextro, Walter (Verlagsschriftenreihe des Heinz Nixdorf Instituts Band 369, Paderborn, 2017)
Zuverlässigkeit, Sicherheit und Verfügbarkeit gewinnen bei der Anwendung von technischen Systemen eine immer größere Bedeutung. Aus diesem Grund hat sich Condition Monitoring, die Zustandsüberwachung eines technischen Produkts, in verschiedenen Industriebranchen etabliert. Die sensorbasierte Überwachung eines Produkts während seiner Betriebsdauer in Kombination mit Condition Monitoring Methoden ermöglichen die Bestimmung des aktuellen Zustands des Produkts und somit eine Diagnose, ob das Produkt seine ihm zugeschriebene Funktion zum aktuellen Zeitpunkt erfüllt. Neben Diagnosen bietet Condition Monitoring auch die Möglichkeit Prognosen aufzustellen, dabei wird die restliche Nutzungsdauer des Produkts aufbauend auf geeigneten Sensordaten geschätzt. So kann eine intelligente Wartungsplanung umgesetzt werden, die im Gegensatz zu klassischen Ansätzen keine festen Wartungsintervalle benötigt und die Nachteile einer rein reaktiven Wartung kompensiert. Stattdessen ist es möglich ein Element bis vor das Ende seiner Lebensdauer zu nutzen und erst dann zu warten, um eine optimale Nutzung zu gewährleisten. Durch eine Bestimmung der verbleibenden Restlebensdauer während des Betriebs ist eine optimale Wartungsplanung möglich, wodurch die Verfügbarkeit und die Auslastung der überwachten Produkte signifikant gesteigert werden kann. In dieser Arbeit soll ein produktspezifisches Condition Monitoring System für Gummi-Metall-Elemente entwickelt werden. Diese Elemente werden zur Federung, Geräusch- und/oder Schwingungsisolation in vielen verschiedenen Anwendungen eingesetzt, wie bspw. in Nutz- und Schienenfahrzeugen oder Windenergieanlagen. In Industrie und Forschung werden bereits Zustandsüberwachungen von Systemen mit integrierten Gummi-Metall-Elementen eingesetzt, allerdings noch keine Condition Monitoring Systeme zur alleinigen Zustandsüberwachung dieser Elemente. Aktuell ist es üblich die Lebensdauer dieser Elemente aufbauend auf beschleunigten Lebensdauerversuchen und Erfahrungswerten abzuschätzen. Mit dem Ziel die Lebensdauer des fokussierten Produkts präziser vorherzusagen und damit eine intelligente Wartungsplanung zu ermöglichen, wird die Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente angestrebt und in dieser Arbeit erläutert.
Keywords: Zustandsüberwachung; Condition Monitoring; Prognose; Gummi-Metall-Elemente; Restlebensdauerschätzung

Modellbasierte Prognose der nutzbaren Restlebensdauer von Gummi-Metall-Elementen - Bender, Amelie; Kimotho, James Kuria; Kohl, Sergej; Sextro, Walter; Reinke, Kai (15. Internationale Schienenfahrzeugtagung)
In vielen verschiedenen Industriezweigen hat sich Condition Monitoring aufgrund seiner finanziellen und sicherheitstechnischen Vorteile bereits etabliert. Um die Verlässlichkeit und die Auslastung zu steigern, sowie um die Lebenszykluskosten zu reduzieren, steigt auch im Schienenfahrzeugbereich die Anzahl an eingesetzten Condition Monitoring Systemen. Studien zu Versagensmodi von Schienenfahrzeugen haben gezeigt, dass Versagensursachen meistens in den Radprofilen oder im Fahrwerk liegen [1]. Wird das Fahrwerk heute mittels Condition Monitoring überwacht, werden hierfür häufig Sensoren an den Wagons angebracht, um bspw. deren Schwingungen zu kontrollieren [2, 3]. In dieser Arbeit liegt der Fokus auf Gummi-Metall-Elementen (GM-Elementen) der Jörn GmbH.; als elastische Lager im Drehgestell sind diese Teil des Fahrwerks eines Schienenfahrzeugs. Mit dem Ziel die Wartungsplanung dieser Elemente zu optimieren, ist untersucht worden, ob diese Elemente einzeln mittels Condition Monitoring überwacht werden können. Die hierfür durchgeführten beschleunigten Lebensdauertests werden im nächsten Abschnitt erläutert. Anschließend werden die modellbasierten Methoden dargestellt, die aufbauend auf den im Versuch aufgezeichneten Daten eine Prognose der nutzbaren Restlebensdauer (RUL, remaining useful lifetime) der GM-Elemente aufstellen. Im letzten Abschnitt folgen eine kurze Zusammenfassung und ein Ausblick.

Neuartiges Konzept zur Lebensdauerprognose von Gummi-Metall-Elementen - Bender, Amelie; Sextro, Walter; Reinke, Kai (VDI-Berichte 2301)
In der Windenergieindustrie haben die Größen Zuverlässigkeit, Sicherheit und Verfügbarkeit eine enorme Bedeutung erlangt aufgrund des Trends Windenergieanlagen zur optimalen Windausnutzung an schwer zugänglichen Positionen aufzustellen, wie bspw. Offshore. Dies führt zu erschwerten Wartungsbedingungen und damit zu höheren Kosten. Der Einsatz von Condition Monitoring hat sich in dieser Industrie etabliert, denn diese Technik ermöglicht eine Zustandsdiagnose des überwachten Systems und eine Prognose seiner nutzbaren Restlebensdauer (remaining useful life: RUL), jeweils basierend auf geeigneten Sensordaten. In dieser Arbeit wird ein Konzept für ein produktspezifisches Condition-Monitoring-System für Gummi-Metall-Elemente (GM-Elemente) vorgestellt, welches den Schwerpunkt auf die Prognose der RUL dieser Elemente setzt. In Windenergieanlagen werden zahlreiche GM-Elemente zur Geräusch- und Schwingungsisolation verwendet. Der Einsatz des hier vorgestellten produktspezifischen Condition-Monitoring-Systems kann somit einen erheblichen Beitrag zum verlässlichen Betrieb von Windenergieanlagen liefern, da die Überwachung einzelner Komponenten in die Zustandsüberwachung der gesamten Anlage integriert und dadurch der Betrieb der Anlage optimiert werden kann. In dieser Arbeit werden einige Herausforderungen diskutiert, die sich bei der Entwicklung eines Condition-Monitoring-Systems für GM-Elemente ergeben. So wird evaluiert, welche Größen sich zur Beschreibung der Alterung eines spezifischen Elements eignen und wie diese gemessen werden können. Temperaturen werden bereits in einigen technischen Systemen, wie auch in Windenergieanlagen, aufgezeichnet und ausgewertet, aber ihr Potential für die Bestimmung der RUL der überwachten Komponente ist noch nicht ausgeschöpft. Hier wird eine Lösungsmöglichkeit vorgestellt, die auf Temperatursensoren aufbaut. Als Grundlage für die Entwicklung des Condition-Monitoring-Systems wurden beschleunigte Lebensdauerversuche der GM-Elemente auf einem Versuchsstand zur Schwingungsanalyse durchgeführt. In diesen Lebensdauerversuchen wird die mechanische Alterung eines GM-Elements über einen kraftgeregelten Hydraulikzylinder erzielt. Dabei wird das Ende der Lebensdauerversuche in einem ersten Schritt über die Wegamplitude des Zylinders bestimmt. Während dieser Versuche wurden diverse Sensoren eingesetzt. Die aufgezeichneten Temperaturdaten zeigen, dass sich Temperaturmessungen eignen die Lebensdauer von GM-Elementen mittels Condition Monitoring Prognosemethoden zu schätzen.

Analysis of pipe vibration in an ultrasonic powder transportationsystem - Dunst, Paul; Hemsel, Tobias; Sextro, Walter (elsevier)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceu-tical and coatings industry the particle sizes of processed powders get smaller and smaller. Fine powdersare primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces, leadingto mostly unwanted agglomeration (clumping) and adhesion to surfaces. Thereby it gets more difficult touse conventional conveyor systems (e.g. pneumatic or vibratory conveyors) for transport. A rather newmethod for transporting these fine powders is based on ultrasonic vibrations, which are used to reducefriction between powder and substrate. Within this contribution an experimental set-up consisting of apipe, a solenoid actuator for axial vibration and an annular piezoelectric actuator for the high frequencyradial vibration of the pipe is described. Since amplitudes of the radial pipe vibration should be as large aspossible to get high effects of friction reduction, the pipe is excited to vibrate in resonance. To determinethe optimum excitation frequency and actuator position the vibration modes and resonance frequenciesof the pipe are calculated and measured. Results are in good accordance.
Keywords: Powder transport Piezoelectrics Ultrasonics Pipe vibration Finite element simulation Fine powder

Multi-dimensional Ultrasonic Copper Bonding – New Challenges for Tool Design - Eichwald, Paul; Althoff, Simon; Schemmel, Reinhard; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (IMAPSource)
In power electronics, copper connector pins are e.g. used to connect control boards with power modules. The new chip generation based on SiC and GaN technology increase the power density of semiconductor modules significantly with junction temperatures reaching 200°C. To enable reliable operation at such high temperature, the soldering of these connector pins should be substituted by a multi-dimensional copper-copper bonding technology. A copper pin welded directly on DBC substrate also simplifies the assembly. With this aim, a proper bond tool and a suitable connector pin geometry are designed. This paper presents a two-dimensional trajectory approach for ultrasonic bonding of copper pieces, e.g. connector pins, with the intention to minimize mechanical stresses exposed to the substrate. This is achieved using a multi-dimensional vibration system with multiple transducers known from flip chip bonding. Applying a planar relative motion between the bonding piece and the substrate increases the induced frictional power compared to one-dimensional excitation. The core of this work is the development of a new tool design which enables a reliable and effective transmission of the multidimensional vibration into the contact area between nail-shaped bonding piece and substrate. For this purpose, different bonding tool as well as bonding piece designs are discussed. A proper bonding tool design is selected based on the simulated alternatives. This tool is examined in bonding experiments and the results are presented. In addition, different grades of hardness for bonding piece and substrate are examined as well as different bonding parameters. Optical inspection of the bonded area shows the emergence of initial micro welds in form of a ring which is growing in direction of the interface boundaries with increasing bonding duration.
Keywords: International Symposium on Microelectronics

Integrated modeling og behavior and reliability in system development - Hentze, Julian; Kaul, Thorben; Grässler, Iris; Sextro, Walter (ICED17, 21st International conference on enginieering design)
The integrated modeling of behavior and reliability in system development delivers a model-based approach for reliability investigation by taking into account the dynamic system behavior as well as the system architecture at different phases of the development process. This approach features an automated synthesis of a reliability model out of a behavior model enabling for the closed loop modeling of degradation of the system and its (dynamic) behavior. The approach is integrated into the development process following Systems Engineering. It is based on standard models used in model-based development methodologies i.e. SysML or Matlab/Simulink. In addition to the theoretical description of the necessary steps the procedure is validated by an application example at two stages of the development process.
Keywords: Design for X (DfX); Product modelling / models; Robust design; Systems Engineering (SE); Reliability

Piezoelectric Inertia Motors—A Critical Review of History, Concepts, Design, Applications, and Perspectives. - Hunstig, Matthias (Actuators. 2017, 6(1)-7.)
Piezoelectric inertia motors also known as stick-slip motors or (smooth) impact drives use the inertia of a body to drive it in small steps by means of an uninterrupted friction contact. In addition to the typical advantages of piezoelectric motors, they are especially suited for miniaturisation due to their simple structure and inherent fine-positioning capability. Originally developed for positioning in microscopy in the 1980s, they have nowadays also found application in mass-produced consumer goods. Recent research results are likely to enable more applications of piezoelectric inertia motors in the future. This contribution gives a critical overview of their historical development, functional principles, and related terminology. The most relevant aspects regarding their design i.e., friction contact, solid state actuator, and electrical excitation are discussed, including aspects of control and simulation. The article closes with an outlook on possible future developments and research perspectives.

Formulation of reliability-related objective functions for design of intelligent mechatronic systems - Kaul, Thorben; Meyer, Tobias; Sextro, Walter (SAGE Journals)
State-of-the-art mechatronic systems offer inherent intelligence that enables them to autonomously adapt their behavior to current environmental conditions and to their own system state. This autonomous behavior adaptation is made possible by software in combination with complex sensor and actuator systems and by sophisticated information processing, all of which make these systems increasingly complex. This increasing complexity makes the design process a challenging task and brings new complex possibilities for operation and maintenance. However, with the risk of increased system complexity also comes the chance to adapt system behavior based on current reliability, which in turn increases reliability. The development of such an adaption strategy requires appropriate methods to evaluate reliability based on currently selected system behavior. A common approach to implement such adaptivity is to base system behavior on different working points that are obtained using multiobjective optimization. During operation, selection among these allows a changed operating strategy. To allow for multiobjective optimization, an accurate system model including system reliability is required. This model is repeatedly evaluated by the optimization algorithm. At present, modeling of system reliability and synchronization of the models of behavior and reliability is a laborious manual task and thus very error-prone. Since system behavior is crucial for system reliability, an integrated model is introduced that integrates system behavior and system reliability. The proposed approach is used to formulate reliability-related objective functions for a clutch test rig that are used to compute feasible working points using multiobjective optimization.
Keywords: Integrated model; reliability; system behavior; Bayesian network; multiobjective optimization

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

MoRFUS: Mobile Reinigungseinheit für Förderketten basierend auf Ultraschall - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (43. Deutsche Jahrestagung für Akustik)
ln der industriellen Fertigung werden zum Transport von Bauteilen häufig Förderketten genutzt. Obwohl die Förderketten meist nicht direkt mit den Arbeitsmedien in Berührung kommen, werden sie indirekt durch vagabundierende Stäube und Pulver, die an der geölten Kette anhaften, im Laufe der Zeit stark verschmutzt. Ein derart im Betrieb verschmutztes Kettenglied ist in Abbildung 1 dargestellt. Um die Lebensdauer der Ketten zu erhöhen und das Herunterfallen von Schmutzpartikel auf die Produkte zu vermeiden, muss die Kette regelmäßig gereinigt werden. Ziel des hier beschriebenen Forschungsvorhabens ist die Entwicklung eines Systems, das in der Lage ist, ein einzelnes Kettenglied in unter 60 s mittels Ultraschall zu reinigen. In [1] wurde in ersten Versuchen nachgewiesen, dass Stabschwinger in Abhängigkeit des Sonotrodenabstands zum Reinigungsobjekt und der Ultraschallamplitude eine intensive Reinigungswirkung entfalten. Das Konzept der Reinigungsanlage sieht deshalb vor, im ersten Schritt die stark verschmutzten Kettenglieder durch ein hochintensives Kavitationsfeld von direkt eingetauchten Stabschwingern vorzureinigen und anschließend schwer zugängliche Be- reiche wie Hinterschneidungen oder Bohrungen mittels konventioneller Tauchschwinger von Verschmutzungen zu befreien. Für den Stabschwinger wird die sogenannte - Sonotrode untersucht; diese wird unter anderem auch in der Sonochemie verwendet. Ein wesentliches Merkmal der Sonotrode ist eine hohe Amplitudenübersetzung bei einer gleichzeitig großen Abstrahlfläche. Neben dem Entwurf mittels der L /2 -Synthese wird die Reinigungswirkung der Sonotrode in Abhängigkeit der Ultraschallamplitude und dem Abstand zum Reinigungsobjekt in einer Versuchsreihe untersucht. Zur genaueren Betrachtung der Reinigungs- mechanismen eines Stabschwingers werden abschließend Hochgeschwindigkeitsaufnahmen vorgestellt und analysieren.
Keywords: wire bonding; dynamic behavior; modeling

Model based optimization of dynamics in adaptive headlamps - Schulze, Sebastian; Sextro, Walter; Kister, K. (Proceedings of the 12th International Symposium on Automotive Lighting 2017)

Entwicklung verlässlicher, intelligenter Systeme - Sextro, Walter; Meyer, Tobias; Kaul, Thorben; Kimotho, James Kuria (VDI-Berichte 2307–28. Tagung Technische Zuverlässigkeit (TTZ 2017) - Entwicklung und Betrieb zuverlässiger Produkte.)
Intelligente technische Systeme sind durch einen erhöhten Funktionsumfang charakterisiert, der diese dazu befähigt, autonom auf wechselnde Umgebungsbedingungen, Anforderungen und inhärente Systemzustände zu reagieren. Dies kann mit den Methoden der Selbstoptimie-rung erreicht werden. Hier werden mit Verfahren der Mehrzieloptimierung mögliche Betriebs-punkte des Systems bestimmt zwischen denen das System im Betrieb autonom auswählt und somit eine Verhaltensadaption erwirkt. Zur Berechnung der Betriebspunkte ist es notwendig ein Modell des Systemverhaltens aufzustellen und das Verhalten hinsichtlich verschiedener, meist konfliktärer, Ziele zu quantifizieren. Bei der Modellierung des Systemverhaltens und der Formulierung der Ziele stellt die Absiche-rung der Verlässlichkeit auf Grund der zunehmenden Systemkomplexität eine große Heraus-forderung dar, der im Entwicklungsprozess begegnet werden muss. Die Implementierung von Selbstoptimierung bietet darüber hinaus in Kombination mit einer Zustandsüberwachung im Betrieb die Möglichkeit einer zuverlässigkeitsbasierten Verhaltensanpassung, deren Potential zu einer Steigerung der Verlässlichkeit genutzt werden kann. In dieser Arbeit werden die Entwicklung intelligenter technischer Systeme und die damit ver-bundenen notwendigen Entwicklungsschritte zur Absicherung der Verlässlichkeit anhand von selbstoptimierenden Systemen betrachtet. Dazu gehören die Formulierung verlässlichkeitsre-levanter Ziele und die Implementierung einer Zustandsüberwachung als Basis für eine zuver-lässigkeitsbasierte Verhaltensanpassung. Es werden auf Grundlage einer Beschreibung der Entwicklungsschritte, Potentiale zur Steigerung der Verlässlichkeit sowie Chancen und zukünf-tige Herausforderungen herausgestellt und diskutiert.
Keywords: intelligente Systeme

"A coupled phase field/diffusion model for upper and lower bainitic transformation" - Düsing, Martin; Mahnken, Rolf (International Journal of Solids and Structures)

"Goal-oriented adaptivity for linear elastic micromorphic continua based on primal and adjoint consistency analysis" - Ju, X.; Mahnken, R. (International Journal for Numerical Methods in Engineering)

Heteroepitaxy of III–V Zinc Blende Semiconductors on Nanopatterned Substrates - Riedl, Thomas; Lindner, Jörg (Nanoscaled Films and Layers)
In the last decade, zinc blende structure III–V semiconductors have been increasingly utilized for the realization of high‐performance optoelectronic applications because of their tunable bandgaps, high carrier mobility and the absence of piezoelectric fields. However, the integration of III–V devices on the Si platform commonly used for CMOS electronic circuits still poses a challenge, due to the large densities of mismatch‐related defects in heteroepitaxial III–V layers grown on planar Si substrates. A promising method to obtain thin III–V layers of high crystalline quality is the growth on nanopatterned substrates. In this approach, defects can be effectively eliminated by elastic lattice relaxation in three dimensions or confined close to the substrate interface by using aspect‐ratio trapping masks. As a result, an etch pit density as low as 3.3 × 10^5 cm^−2 and a flat surface of submicron GaAs layers have been accomplished by growth onto a SiO2 nanohole film patterned Si(001) substrate, where the threading defects are trapped at the SiO2 mask sidewalls. An open issue that remains to be resolved is to gain a better understanding of the interplay between mask shape, growth conditions and formation of coalescence defects during mask overgrowth in order to achieve thin device quality III–V layers

Joining self-assembly techniques: A route to hierarchical nanopores - Brassat, Katharina; Lindner, Jörg

Micro- and nanopatterned surfaces with tailored chemical and topographical contrast by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg

Tailored antidot patterns created by nanosphere lithography for bioapplications - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Morphological properties of nanopillar patterned Si surfaces obtained by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Lindner, Jörg

InAs heteroepitaxy on GaAs patterned by nanosphere lithography - Kunnathully, Vinay; Riedl, Thomas; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Group III arsenide heteroepitaxy on Si(111) using SiNx nanohole masks patterned by nanosphere lithography - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Strain and strain energy in axial-heteroepitaxial GaAs/InAs nanopillars analyzed by atomistic and continuum elastic calculations - Riedl, Thomas; Lindner, Jörg

The influence of the sphere material on the opening size distribution of nanosphere lithography masks - Riedl, Thomas; Lindner, Jörg

Evolution of the opening size of nanosphere lithography masks during thermal annealing - Riedl, Thomas; Kunnathully, Vinay; Lindner, Jörg

Strain Compensation in Single ZnSe/CdSe Quantum Wells: Analytical Model and Experimental Evidence - Rieger, Torsten; Riedl, Thomas; Neumann, Elmar; Grützmacher, Detlev; Lindner, Jörg; Pawlis, Alexander (ACS Applied Materials & Interfaces)

Strain effects on the heteroepitaxy of III-V compound semiconductors on nanopatterned surfaces - Lindner, Jörg; Riedl, Thomas

Ion Beam Modification of Self-Organized Nanostructures - Lindner, Jörg

Bioinspired material design by hierarchical self-assembly on prepatterned surfaces - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Regular surface nanopatterning with nanosphere lithography, block copolymer lithography and cominations of both - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Optimisation of stability and charge transferability of ferrocene-encapsulated carbon nanotubes - Prajongtat, Pongthep; Sriyab, Suwannee; Zentgraf, Thomas; Hannongbua, Supa (Molecular Physics)

Verzerrte Online-Produktbewertungen - Literaturüberblick - Hamdeev, Erna

Retourenmanagement zur Steigerung des Kundenwerts - Garnefeld, Ina; Boehm, Eva; Feider, Lena (Kundenwert)

Der Einfluss steuerlicher Verlustverrechnung auf Investitionsentscheidungen bei Risiko unter Berücksichtigung präskriptiver und deskriptiver Verhaltenselemente - Mehrmann, Annika

Die Bewertung der Steuerstrategie von Unternehmen - Brinkmann, Bastian

Die Initiative der EU zum öffentlichen Country-by-Country Reporting - Bornemann, Tobias; Eberhartinger, Eva (RWZ- Zeitschrift für Recht und Rechnungswesen)

Capital Charge Rates, Investment Incentives and Taxation - Bauer, Thomas; Kourouxous, Thomas (European Accounting Review)
This paper studies the impact of personal and corporate income taxation on capital charge rates in a delegation setting with a risk-averse manager. If the investment level influences the riskiness of the investment project, the capital charge rate deviates from the firm's cost of capital and depends crucially on the manager's personal income tax rate. Contradicting conventional wisdom, we find that a higher personal income tax rate induces higher investment expenditures and, surprisingly, increases the capital charge rate. The countervailing effect that a higher capital charge rate induces higher and not lower investment expenditures persists for pre-tax and after-tax performance measures as well as when the tax deductibility of managerial compensation is limited. Corporate income tax causes a similar effect only in the case of limited tax deductibility of compensation. Our insights remain valid regardless of the financing structure and the risk attitude of the investors.

Design and Evaluation of a Model-Driven Decision Support System for Repurposing Electric Vehicle Batteries - Klör, B; Monhof, M; Beverungen, Daniel; Bräuer, S (European Journal of Information Systems (EJIS))

End-of-Life Solutions für eCar-Batterien --- Entwicklung hybrider Leistungsbündel und Informationssysteme zur Entscheidungsunterstützung (EOL-IS) - Becker, Jörg; Monhof, Markus; Beverungen, Daniel; Bräuer, Sebastian; Klör, Benjamin; Plenter, Florian (Dienstleistungen als Erfolgsfaktor für Elektromobilität. Ergebnisse aus dem Förderschwerpunkt “Dienstleistungsinnovationen für Elektromobilität”)

Informationsmodellierung in Dienstleistungssystemen - Beverungen, Daniel; Matzner, Martin (Handbuch Dienstleistungsmanagement)